Signalized intersection simulation and traffic signal control for a complex intersection in Gothenburg Analysis of signal control system in Ullevigatan – Skånegatan intersection using PTV Vissim - MURALEEDHARAN, ARYA (My University, 2023)
Signalized intersections play a key role in regulating effective traffic flow and reducing traffic congestion. This master’sthesis focuses on the analysis of the signal controller at one of the most complex intersections in Gothenburg, the Ullevigatan- Skånegatan intersection. The intersection model was created using PTV Vissim traffic simulation software. Three scenarios were created and simulated in Vissim. The first one is the model with the current signal control plan at the intersection, which is the actuated signal control using the LHOVRA concept. The second one is the model with an actuated signal controller by vehicle actuated programming (VAP). The third model is the fixed-time signal controller model. These three models were simulated, and the results were analyzed. The analysis was done by evaluating performance measures such as queue delay, queue length, and vehicle travel time. This analysis provides a deep understanding of the performance at the intersection. These simulation results identified the potential area for signal optimization time improvement. This research provides the effects of different signal controller methods, such as actuated signal controllers and fixed-time signal controllers. The analysis explores whether the implementation of an actuated signal controller with VAP has the potential to improve overall efficiency at the intersections as well as reduce delays.
Keywords: Signalized intersection, PTV Vissim, actuated signals, traffic signal controller.